Consumo, digestibilidade aparente de nutrientes e balanços de nitrogênio e hídrico de ovinos alimentados com silagens de cultivares de capim-búfel - Souza, R. A.; Voltolini, T. V.; Araújo, G. G L; Pereira, L. G R; Moraes, S. A.; Mistura, C.; Belem, K. V J; Moreno, G. M B [UNESP] (FapUNIFESP (SciELO), 2013)
The objective of this present experiment was to determine intake and apparent digestibility of dry matter and nutrients, nitrogen (NB) and water balances (WB) of sheep fed with buffel grass silages. The buffel grass cultivars used were Tanzania, Buchuma and Biloela. 21 male, castrated, crossbred Santa Ines x Non defined genotype sheep, with initial body weight of 31.8±3.16kg were used, kept in metabolic cages. The experimental design was completely randomized with seven replicates. No differences were observed in dry matter intake in g/day (919.2) and % of body weight (2.9). In general, digestibility coefficients of dry matter varied from 37.7% to 60.0%. The NB and WB were positive, with higher NB values in sheep fed with Tanzania (5.1g/day) and Biloela (3.9g/day) and higher WB in animals fed with Buchuma (1.38kg/animal/day) and Biloela (1.42kg/animal/day). All cultivars of buffel grass evaluated (Tanzania, Buchuma and Biloela) presented adequate chemical composition, where the silage of buffel grass used corresponded to 60% of the total daily water intake by sheep.
Intake, apparent digestibility of nutrients and nitrogen and water balances of sheep fed with buffel grass cultivars silages
Keywords: Cenchrus ciliaris; Conservation of forage; Nutritive value